Socio-Demographic, Economic Characteristics and Safe Motherhood among the Reproductive Age of Women in Danuwar Community of Lalitpur, Nepal - Devkota, Bijaya Mani; Bohara, Pradeep Kumar (Kutumbha vani, 2025)
This study is the combinations of socio-demographic and economic determinants that lead to certain fertility behaviors and safe motherhood practices among women of reproductive age in the Danuwar community, Lalitpur, Nepal. Even though there have been national improvements regarding reduction in birth rates and maternal health, the disadvantaged groups still suffer from the same problems through no fault of their own because of limited education, economic instability, and cultural impositions. The methodological approach adopted by the study was a cross-sectional descriptive study which involved structured interviews with 289 married women aged 15-49 years. Descriptive statistics were the tools for analyzing the data, with the latter being employed to find out the associations between socio-demographic variables, fertility behavior, and safe motherhood indicators. The results indicated that a large number of the respondents were in the age group of 25-34 years, which constituted 47.2 percent of the total, and the rest, that is, 52.8 percent, had given birth to two to six children. Awareness of and reliance on contraceptives were quite high (57.1% & 78.3%), and nearly all the women (97.5%) recognized that education would help in fertility reduction. But the liking for a male child (57.8%) and the influence of religion on family size (36%) were still significant factors. The majority (79.5%) were informed about the government's family planning programs, while migration, disaster, and employment factors were found to be significantly related to fertility (p < 0.001). As for safe motherhood, 61.4 percent of births were attended by skilled health professionals, and more than 70 percent of the women had access to antenatal and postnatal care. Moreover, the percentage of availability of maternal and general health services was also high, with 84.3 percent and 98 percent respectively. Fertility patterns and health of mothers among Danuwar women are determined by the intermingling of social, demographic, economic, and cultural aspects. Economic empowerment, women's education, and culturally sensitive health interventions should be the primary interventions in Nepal's marginalized groups to attain equitable reproductive health and safe motherhood.